2016
DOI: 10.1128/iai.00337-16
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Infection Enhances Erythropoietin Production by the Kidney and Liver, Which Correlates with Elevated Bacterial Burdens

Abstract: Salmonella infection profoundly affects host erythroid development, but the mechanisms responsible for this effect remain poorly understood. We monitored the impact of Salmonella infection on erythroid development and found that systemic infection induced anemia, splenomegaly, elevated erythropoietin (EPO) levels, and extramedullary erythropoiesis in a process independent of Salmonella pathogenicity island 2 (SPI2) or flagellin. The circulating EPO level was also constitutively higher in mice lacking the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Overall, our previous studies have revealed that neonatal vulnerability to infection results from the temporary existence of immunosuppressive CD71 + erythroid cells. In agreement, a recent study has shown a marked expansion of erythroid precursors (CD71 + TER119 + ) in murine spleens following Salmonella infection and demonstrated that presence of these cells was associated with enhanced bacterial persistence [9]. More recently, the immunomodulatory properties of CD71 + erythroid cells in cord blood of preterm versus full-term newborns have been investigated [13].…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Overall, our previous studies have revealed that neonatal vulnerability to infection results from the temporary existence of immunosuppressive CD71 + erythroid cells. In agreement, a recent study has shown a marked expansion of erythroid precursors (CD71 + TER119 + ) in murine spleens following Salmonella infection and demonstrated that presence of these cells was associated with enhanced bacterial persistence [9]. More recently, the immunomodulatory properties of CD71 + erythroid cells in cord blood of preterm versus full-term newborns have been investigated [13].…”
Section: Introductionmentioning
confidence: 58%
“…Subsequent studies towards understanding the immunomodulatory mechanism of these cells showed that TGF-β [6] and direct cell–cell interactions might partially be involved for their immunosuppressive effects [7]. Moreover, it has been suggested that erythroid precursors promote polarization of naive CD4 + T cells to different T cell subtypes [3,8] and may alter the T-helper 1/2 (Th1/Th2) cytokine balance toward a Th2 phenotype in newborns [9]. In agreement, we have recently discovered that CD71 + erythroid cells are enriched in newborns and, because of their immunosuppressive properties, impair both the innate and adaptive immune responses in newborns [1012].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory signaling through TLRs plays a key role in this response as mice with mutations in the downstream signaling molecules, Myd88 and TRIF, fail to induce splenic erythropoiesis after infection. Salmonella infection also increases Epo production by the kidney and liver, which contributes to the increase in splenic stress erythropoiesis [99][100][101]. Like the infection models, sterile inflammation models show increased splenic erythropoiesis.…”
Section: Inflammation Induces Stress Erythropoiesismentioning
confidence: 98%
“…Immune potency of these CD71+ erythroid cells was also observed in neonatal salmonella infection but it seemed to have both positive and negative consequences for host immunity. 44 Immunosuppression mediated by CD71+ erythroid cells is also crucial for homeostasis in the perinatal period, as it has been shown to bring down TNF-alpha and IFN-gamma production through arginase-2 activity and PD-1/programmed death ligand-1 (PDL-1), contributing to fetomaternal tolerance. 22 The critical window of erythropoiesis in the neonatal period suggests erythroid lineage cells may play an important role in neonatal immunity.…”
Section: Erythroid Lineage Cells and Neonatal Immunitymentioning
confidence: 99%